2017
DOI: 10.1371/journal.pone.0187988
|View full text |Cite
|
Sign up to set email alerts
|

Topical anaesthesia reduces sensitivity of castration wounds in neonatal piglets

Abstract: The aim of this study was to do determine the efficacy of the topical anaesthetic Tri-Solfen® in the amelioration of the pain of castration in piglets. The trial was conducted over a three day period, and blocked across six litters with 12 piglets treated on days one and two, and 16 on day three. The piglets were randomly allocated by weight and litter to 1 of 4 treatment groups: (i) sham castration (SHAM; n = 10); (ii) surgical castration with no anaesthetic intervention (CAST; n = 10); (iii) surgical castrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(43 citation statements)
references
References 22 publications
3
40
0
Order By: Relevance
“…Following data collection, all animals were treated topically with 4.5 mL Tri-Solfen®topical anaesthetic (Bayer Animal Health, Pymble, NSW, Australia) by inserting the provided nozzle into the post-castration scrotal incision [23]. Lambs were also administered meloxicam subcutaneously at 1 mg/kg (Boehringer Ingelheim Pty Limited, North Ryde, NSW, Australia).…”
Section: Electroencephalography Recordingmentioning
confidence: 99%
“…Following data collection, all animals were treated topically with 4.5 mL Tri-Solfen®topical anaesthetic (Bayer Animal Health, Pymble, NSW, Australia) by inserting the provided nozzle into the post-castration scrotal incision [23]. Lambs were also administered meloxicam subcutaneously at 1 mg/kg (Boehringer Ingelheim Pty Limited, North Ryde, NSW, Australia).…”
Section: Electroencephalography Recordingmentioning
confidence: 99%
“…Importantly, the application of the combination topical anaesthetic formulation delivered directly onto the wound peri‐operatively or immediately postoperatively was immediately recognised to have broader applications in livestock husbandry. Following extensive research trials involving many routine aversive husbandry procedures, Tri‐Solfen has now been demonstrated to be safe and efficacious in managing pain and improving healing of acute surgical wounds incurred during surgical castration and tail docking of lambs, surgical castration and dehorning of calves, and surgical castration of piglets . It is also proving effective in chronic wound conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Neural markers of pain mitigation, such as the expression of the c-fos gene and its protein product, Fos, in neurons of the spinal cord [75], are significantly reduced when piglets are castrated under effective local or general anaesthesia, as compared with piglets castrated without anaesthesia [43]. Furthermore, this is associated with a dramatic reduction in the nociceptive motor and vocal response to castration [31,32,74]. Additionally, reduced postoperative hyperalgesia has been documented in local anaesthetic-treated piglets [31,32].…”
Section: Physiological Measurements Of Pain In Pigletsmentioning
confidence: 99%
“…Furthermore, this is associated with a dramatic reduction in the nociceptive motor and vocal response to castration [31,32,74]. Additionally, reduced postoperative hyperalgesia has been documented in local anaesthetic-treated piglets [31,32]. Together, these factors are considered to indicate that biomarkers of activation of the HPA axis, and inflammatory response lack specificity for pain mitigating effects of local and general anaesthetics, and are poor indicators of pain in piglets castrated under general or local anaesthesia [1].…”
Section: Physiological Measurements Of Pain In Pigletsmentioning
confidence: 99%
See 1 more Smart Citation